Obsessive–Compulsive Personality Symptoms Predict Poorer Response to Gamma Ventral Capsulotomy for Intractable OCD - Copetti, Maria Eugênia; Lopes, Antonio C.; Requena, Guaraci; Johnson, Isaac N. S.; Greenberg, Benjamin D.; Noren, Georg; McLaughlin, Nicole C. R.; Shavitt, Roseli G.; Miguel, Eurípedes C.; Batistuzzo, Marcelo C.; Hoexter, Marcelo Q. (Frontiers in Psychiatry, 2020)
Gamma ventral capsulotomy (GVC) is a radiosurgical procedure which aims to create lesions in the ventral part of the anterior limb of the internal capsule (ALIC). It has been used as a treatment option for patients with intractable obsessive–compulsive disorder (OCD) who do not respond to several first-line treatments attempts. However, changes in personality disorder symptoms after GVC have not been investigated. The aims of this study are to investigate changes in personality disorder symptoms after GVC and to search for baseline personality disorder symptoms that may predict clinical response to GVC. Fourteen treatment-intractable OCD patients who underwent GVC completed the Structured Clinical Interview for DSM-IV Personality Disorders (SCID-II) at baseline and one year after the procedure. Wilcoxon signed-rank test was performed to investigate personality disorder symptom changes before and after surgery. Linear regression models were utilized to predict treatment response, using baseline personality disorder symptoms as independent variables. We did not observe any quantitative changes in personality disorder symptoms after GVC, compared with baseline. Higher severity of obsessive-compulsive personality disorder symptoms at baseline was correlated with worse treatment response after GVC for OCD (β = −0.085, t-value = −2.52, p-value = 0.027). These findings advocate for the safety of the GVC procedure in this specific population of intractable OCD patients, in terms of personality disorder symptom changes. They also highlight the importance of taking into account the severity of obsessive–compulsive personality disorder symptoms when GVC is indicated for intractable OCD patients.